The perfect pill : 10 steps to build a strong healthcare brand - Chaudhari, Gauri (Thousand Oaks : SAGE Publishing, 2020)
"'How can I build my brand when it is just a me-too?' is the quintessential question asked by every health care professional in India. With over a hundred brands of the same kind and a plethora of patented yet very similar molecules, brand building and creating a competitive advantage are challenging in the Indian health care industry. The Perfect Pill propagates a robust, 10-step, health care brand-building model that helps you create the much-needed differentiation that results in unique customer value. The steps suggested in the book help in establishing an ultimate win-win situation for patients, doctors, and sales and marketing teams. 'Indian pharmaceutical Industry is rightly called the pharmacy of the world. Brand is fundamental and patient is at the center of what we do in this industry. This book is timely and puts focus on patient insights, which is key in taking forward the agenda of value creation both for patients and companies. The Perfect Pill will be a useful book for all interested in the health care space and will serve as thought starter for making a real difference in this sunrise sector.' Sudarshan Jain Secretary General, Indian Pharmaceutical Alliance and Former MD, Abbott Healthcare Gauri Chaudhari is the Co-founder of Brand Innerworld, the health care brand-building consultancy"--